O "perigo alemão" no Brasil da Primeira Guerra Mundial (1914-1918): a visão da imprensa de Santa Catarina - Cenci, Jones (2023)
The study of an alleged Pan-German plan for domination and annexation of territories in South America, particularly from the states of Paraná, Santa Catarina and Rio Grande do Sul, it became popularly known as "German Danger". The elements that constructed and deconstructed this idea were addressed in this work, through the press of Santa Catarina during the First World War, a perspective that required a detailed temporal cut, an attentive look, which seeks through details, an understanding of the sociocultural, ethnic and political aspects that made up that specific context. Through the analysis of Santa Catarina periodicals supporting both sides of the conflict (Germanophiles and Aliadophiles), we understand in parts, the resistance to the integration of the population of German origin in Brazil, the nationalist spirit of the time, attached parallel to the spread of the Pan-German threat in Latin America: How the "German Danger" was discussed by historiography at the time of the First World War? Like the Press at the time of the First Did the World War help build the idea that the "German Danger" really existed? How the press tried to deconstruct the ideology of the “German Danger”? These are issues that have been worked on and aim to introduce this subject, starting this path that requires different bridges to cross the gaps historical and through them we understand if the "German Danger" really existed, or if it is part of an attempt to hold the Germans living here and their descendants responsible for the acts carried out by the Germany in the First World War. As research sources we used documentation from the collection of newspapers and magazines digitized by the National Library. The power of the press in disseminating ideas guides this study. The press as a driver of historical reflection, its ability to bring the reader closer to the news, the possibility of offering multiple views of the world, whether in intensity or in perspective, where history and press contemplate each other.